Employee Payroll Accounting System and Procedure Analysis - Salsabila, Putri Aisyah (Advances in Applied Accounting Research, 2023)
This study aims to determine the payroll accounting system and procedures for employees at PT. Makassar Cellular Telecommunications. Sources of data used are primary data with data collection techniques of observation, interviews, and documentation. Data analysis used descriptive qualitative technique, namely descriptive analytical method that compares the existing theory with the results of the research collected. The results of the study indicate that the payroll accounting system includes related functions, namely staffing, payroll section maker, timekeeping section, accounting section and finance section. Documents used in the payroll accounting system include supporting documents for salary changes, recapitulation of payroll registers, salary statements and proof of cash outflows. The accounting records used are general journals. Payroll procedures include procedures for recording time, procedures for making payroll, recording procedures for making proof of payment and procedures for paying salaries. Internal controls implemented include organization, authorization systems and recording procedures as well as healthy practices. This is also supported by the company's technological developments. Based on the results of these studies, it is known that the payroll accounting system of PT. Makassar Cellular Telecommunication has been effective and efficient.